Association of type 2 diabetes remission and risk of cardiovascular disease in pre-defined subgroups - Hounkpatin, H; Stuart, B; Farmer, A; Dambha-Miller, H (Wiley, 2021)
Aim: To quantify the association between type 2 diabetes remission and 5-year incidence of cardiovascular disease outcomes, overall and in pre-defined subgroups. Methods: Retrospective cohort analysis of 60,287 adults with type 2 diabetes from the Care and Health Information Analytics (CHIA) database. Multivariable Cox models were used to assess the association between remission within the first two years of follow-up and incidence of cardiovascular disease (CVD) outcomes including events, microvascular and macrovascular complications at 7-year follow-up. Effect modification by age, sex, diabetes duration, pre-existing CVD, baseline body mass index (BMI) and HbA1c level were assessed. Results: 7489 (12.4%) people achieved remission during the first two years of follow-up. Overall, remission was associated with lower risk of CVD outcomes. Remission was associated with lower risk of microvascular complications for younger compared to older age groups (for example, aHR: 0.59 (0.41-0.84) and aHR: 0.78 (0.67-0.92) for those aged <45 years and 75-84 years, respectively). Among those achieving remission, those with no or 1-2 comorbidities had lower risk of microvascular complications (aHR: 0.65 (0.56-0.75) compared to those with more than 3 comorbidities (aHR: 0.83 (0.69-0.99), respectively). There were no significant interactions in the remaining subgroups or for models assessing CVD events or macrovascular complications. Conclusions: Achieving remission of type 2 diabetes is associated with a lower risk of microvascular complications, particularly for younger groups and those with fewer comorbidities. Targeted interventions that focus on promoting remission in these groups may reduce the impact of microvascular complications and associated health costs.